The Paris wife : a novel - McLain, Paula (Ballantine Books, 2011)
Meeting through mutual friends in Chicago, Hadley is intrigued by brash "beautiful boy" Ernest Hemingway, and after a brief courtship and small wedding, they take off for Paris, where Hadley makes a convincing transformation from an overprotected child to a game and brave young woman who puts up with impoverished living conditions and shattering loneliness to prop up her husband's career.